2022
DOI: 10.1093/cercor/bhac445
|View full text |Cite
|
Sign up to set email alerts
|

A stable sensory map emerges from a dynamic equilibrium of neurons with unstable tuning properties

Abstract: Recent long-term measurements of neuronal activity have revealed that, despite stability in large-scale topographic maps, the tuning properties of individual cortical neurons can undergo substantial reformatting over days. To shed light on this apparent contradiction, we captured the sound response dynamics of auditory cortical neurons using repeated 2-photon calcium imaging in awake mice. We measured sound-evoked responses to a set of pure tone and complex sound stimuli in more than 20,000 auditory cortex neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 57 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…We next examined the relative stability of subpopulation membership for individual neurons, looking both at what neurons belonging to a given subpopulation became on subsequent sessions ( Figure 5A ) and which subpopulation a neuron belonged to in prior sessions ( Figure 5B ). We quantified stability by calculating the frequency with which neurons changed touch subpopulation 25 ( Figure 5C ). Neurons that were non-touch responsive or unidirectional single whisker on a given session were most likely to have been non-touch responsive on the prior session.…”
Section: Resultsmentioning
confidence: 99%
“…We next examined the relative stability of subpopulation membership for individual neurons, looking both at what neurons belonging to a given subpopulation became on subsequent sessions ( Figure 5A ) and which subpopulation a neuron belonged to in prior sessions ( Figure 5B ). We quantified stability by calculating the frequency with which neurons changed touch subpopulation 25 ( Figure 5C ). Neurons that were non-touch responsive or unidirectional single whisker on a given session were most likely to have been non-touch responsive on the prior session.…”
Section: Resultsmentioning
confidence: 99%
“…Other electrophysiological studies focusing on more basic measures of stimulus selectivity, such as frequency tuning, have suggested that neuronal response properties may be stable for days or weeks in awake animals implanted with electrode arrays (Williams et al, 1999;Witte et al, 1999). More recently, in vivo two-photon calcium imaging has been used to track sound-evoked responses of auditory cortical neurons across many days (Kato et al, 2015;Aschauer et al, 2022;Chambers et al, 2022). Selectivity for simple and complex sounds was reported to be relatively stable across days at the population level but unstable at the single-neuron level (Aschauer et al, 2022;Chambers et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in vivo two-photon calcium imaging has been used to track sound-evoked responses of auditory cortical neurons across many days (Kato et al, 2015;Aschauer et al, 2022;Chambers et al, 2022). Selectivity for simple and complex sounds was reported to be relatively stable across days at the population level but unstable at the single-neuron level (Aschauer et al, 2022;Chambers et al, 2022). Much of this instability in single-neuron stimulus selectivity appears to arise from frequently quiescent neurons that might not be detected in electrophysiological studies; more active neurons may maintain more consistent stimulus selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations